Answer:
(2 x +1) ( x + 1) = 2 x² + 3 x + 1
Step-by-step explanation:
The steops used to find the product of (2 x + 1) (x + 1) are
=( 2 x )× x + (2 x) × 1 + x + 1
= 2 x² + 2 x + x + 1
= 2 x² + 3 x + 1
Answer:
I think its B but I have very little evidence. Don't even put B but I was just saying I think it is.
Step-by-step explanation:
To multiply a fraction, you simply multiply across the top and across the bottom.
-3 *-4 = 12
5 * 7 = 35
Final Answer: 12/35
Answer:
30,60,90 triangle, which is the lengths 1 √
3
, and 2
respectively. This is what I have got so far: Using the 30-60-90 Ratio
Step-by-step explanation: